The Potential of The Electronic Information-Educational Environment of A University In Professional Education: Trends And Prospects - Vladimirovna Barashkina, Elena (2021)
At present, the educational paradigm of professional education shows a tendency to change towards the creation of electronic information-educational environments of universities. This trend is determined by the global conditions of the COVID-19 pandemic, as well as national state interests. The problem of the study lies in substantiating the potential of the electronic information-educational environment of a university in professional education in the context of global changes. The goal of the study is to reveal the potential of university electronic information-educational environments in professional education and identify the trends and perspectives of creating electronic information-educational environments of higher education institutions. Results: A characteristic of the electronic information-educational environment of a university is provided, and its components and resources are identified. The predominant tendencies in the development of e-learning in modern professional education are revealed. The advantages of electronic information-educational environments of universities in professional education are allocated. The prospects for the development of electronic information environments of universities are substantiated.